Coexistence of Magnetic and Electric Orderings in the Metal-Formate Frameworks of [NH][M(HCOO)]. - Guan-Cheng Xu; Wen Zhang; Xiao-Ming Ma; Yi-Hong Chen; Li Zhang; Hong-Ling Cai; Zhe-Ming Wang; Ren-Gen Xiong; Song Gao (Journal of the American Chemical Society, 2011)
A family of three-dimensional chiral metal-formate frameworks of [NH][M(HCOO) ] (M = Mn, Fe, Co, Ni, and Zn) displays paraelectric to ferroelectric phase transitions between 191 and 254 K, triggered by disorder-order transitions of NH cations and their displacement within the framework channels, combined with spin-canted antiferromagnetic ordering within 8-30 K for the magnetic members, providing a new class of metal-organic frameworks showing the coexistence of magnetic and electric orderings.